Espécies de flebotomíneos no estado do Amapá, Brasil - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá)
Phlebotomines are insects with medical importance, since they can transmit Leishmania. They are Diptera from Phlebotominae subfamily belonging to the Psycodidae family, popular know as sand flies. The phlebotomines are diferentialy distributed in Brazil as well as in other countries, being their biological diversity a result of interaction between ecological interactions and geographic characteristics. This brings up a medical importance of species distribution across endemic areas of Leishmaniose as occours in Amapa State, Brazil. This research aimed to identify the ecological phlebotomines distribution in the Amapá State, on the Amazon region of Brazil, as well as to identify in which cities of the State have medical importat phlebotomines. The insects was collected using CDC-type light traps, located at 50m, 100m and 150m far from an forest border, in all cities of Amapá State. They were stored in ethanol 70%, and the DNA was extracted by Proteinase K followed by phenol/chloroform method. We used cytochrome C oxidase subunit I (COI) as template to amplify a 550-650 base pairs fragment, which was sequenced with Sanger’s method. The sequences obtained was analysed by BOLD and NCBI databases. As result, it was obtained 599 phlebotomines, with 340 females and 259 males. After the PCR amplification of COI gene, it was possible to obtain 332 positive samples, and 103 of them was submitted to Sanger sequencing. A total of 84 sequenced samples was submitted to databases, and it was possible to identify 67 specimens al specie level and 17 at genera level. There was 15 species of sandflies, with Nyssomyia antunesi as the most frequent. The genera more frequent was Nyssomyia, Trichopygomyia and Bichromomyia. The medical importat speceis colected was Bichromomyia flaviscutellata, Nyssomyia umbratilis and Psychodopygus squamiventris squamiventris. Our results show that the COI gene can be used as an efficient tool to identify sandflies species; however, it can not be used as the only tool, since there was some inconsistencies in the genetic identification, including databases limitations and erros, so we can suggest that molecular identification could be used in combination with morphological analisys.
Keywords: Insetos - Amapá; Flebotomíneo - Vetor biológico; Leishmanioses - Vetores; Entomologia médica; CNPQ::CIENCIAS DA SAUDE